Stochastic estimation of total radiated power from PCB signal/PDN layout using EMI radiation resistance. (October 2021) - Mehri, Milad
Abstract: In this article, a stochastic model is proposed for estimation of electromagnetic radiated emission from printed circuit board (PCB) layout. Considering the arbitrary nature of the PCB layout by radiation resistance, the radiated power density is estimated analytically. The model employs stochastic passing signals as layout trace excitation. The approach is conducted on a designed and fabricated test board. The total radiated power from the PCB layout can be as high 11.5 nW in 2.4GHz–2.5 GHz and 2.8uW in 1 MHz to 3 GHz. An important achievement of the model is its fast estimation of total radiated power for a given PCB layout, rather time/cost consuming experimental measurements and software simulations. For the designed test board, the full-wave simulation time lasts 5 h, while the proposed mathematic model gives the result within 30s on a device with Intel Core i5 processor and 8 GB RAM. The approach can be considered as a fast and preliminary verification step in estimation of radiated emission from PCB layout.